Fragile cities from a geographical perspective The city of Baghdad as a model: A study in political geography - Ismail Ibrahim, Dr.maher (Al-Adab Journal, 2021)
The city of Baghdad is a city with a cultural, intellectual and historical depth, represents the center of population weight at the state level, being the capital and representing a major center for commercial and economic services, providing job opportunities, which made it a center for attracting residents from all governorates. It occupies a geographic location in central of Iraq, surrounded by different geographical environments, this means that it occupies a geographical location that represents a knot branching from the transport and transportation routes that connect all the governorates of Iraq. Baghdad has prospered and developed because of its geographical location, which represents a fertile region that provides it with all the agricultural products it needs. Baghdad was subjected to an abnormal movement of the population because of security reasons due to the conditions that Iraq went through, as well as the administrative changes that added many districts and areas, which led to the expansion of its geographical area, that effect emergence of negative economic, social consequences and the deterioration of its reality, thus provide the conditions and characteristics make up the fragility of the city.